Colorimetric polarity chemosensor based on a organometal halide perovskite functional dye. (October 2016) - Kim, Jong H.; Kim, Sung-Hoon
Abstract: We have investigated polarity sensing of organometal halide CH3 NH3 PbI3 perovskite functional dye based on hydrogen bonds between alcohols and polar units in perovskite. Upon exposure of alcohol solvents, perovskite film showed a drastic visible color change with different changing time depending on the polarities of alcohols. From the kinetic study of the reaction between perovskite dye and alcohols having different polarities, efficiency of hydrogen-bonding interactions between them were clearly revealed to be the main sensing mechanism, which enables effective discrimination of polarities by naked eyes. This study suggests a novel and practical sensing platform for highly sensitive colorimetric polarity chemosensors. Highlights: Organometal halide perovskite is used as a colorimetric chemosensor. Polar species can be detected based on hydrogen bonding interaction with perovskite. Color change rate of perovskite by alcohol is proportionally increased with increased polarity of alcohols.